2022
DOI: 10.1155/2022/5907900
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis and Research on Audience Satisfaction of Performing Arts Projects in Tourist Scenic Spots Based on the ASCI Model and Big Data

Abstract: The development trend of tourism performance networking, although convenient for audience consumption, also makes the performance information present the development trend of big data. In the mass of information, how to accurately locate products and improve audience satisfaction is an urgent problem to be solved. In order to better explore the evaluation of tourism performance by the customer satisfaction evaluation model, analyze the development prospect of tourism in Jiangxi Province in the future, improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Moreover, some researchers point out that online reviews about products could influence consumers’ purchasing behavior ( Zhao et al, 2020 ; Li et al, 2022 ). However, merchants often increase their business profits by adding comments that confuse the real experience of the commodities ( Ding and Yu, 2022 ). Therefore, the following hypotheses are made:…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, some researchers point out that online reviews about products could influence consumers’ purchasing behavior ( Zhao et al, 2020 ; Li et al, 2022 ). However, merchants often increase their business profits by adding comments that confuse the real experience of the commodities ( Ding and Yu, 2022 ). Therefore, the following hypotheses are made:…”
Section: Methodsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%